The novel atypical dopamine transport inhibitor CT-005404 has pro-motivational effects in neurochemical and inflammatory models of effort-based dysfunctions related to psychopathology. (1st February 2021) - Rotolo, Renee A.; Presby, Rose E.; Tracy, Olivia; Asar, Sokaina; Yang, Jen-Hau; Correa, Merce; Murray, Fraser; Salamone, John D.
Abstract: Depressed individuals suffer from effort-related motivational symptoms such as anergia and fatigue, which are resistant to treatment with many common antidepressants. While drugs that block dopamine transport (DAT) reportedly have positive motivational effects, DAT inhibitors such as cocaine and amphetamines produce undesirable side effects. Thus, there is a need to develop and characterize novel atypical DAT inhibitors with unique and selective binding profiles. Rodent effort-based choice tasks provide useful models of motivational dysfunctions. With these tasks, animals choose between a high-effort instrumental action leading to highly valued reinforcement vs. a low effort/low reward option. The present studies focused on the initial characterization of a novel atypical DAT inhibitor, CT-005404, which binds to DAT with high selectivity relative to serotonin and norepinephrine transport, and produces long-term elevations of extracellular DA. CT-005404 was assessed for its ability to attenuate the effort-related motivational effects of the DA depleting agent tetrabenazine and the pro-inflammatory cytokine interleukin-1β (IL-1β) using a fixed ratio 5/chow feeding choice test. Tetrabenazine (1.0 mg/kg i.p.) shifted choice behavior, decreasing lever pressing and increasing chow intake. IL-1β (4.0 μg/kg i.p.) also decreased lever pressing. CT-005404 was co-administered (7.5–30.0 mg/kg p.o.) with either tetrabenazine or IL-1β, and the 15.0 and 30.0 mg/kg doses significantly reversed the effects of tetrabenazine and IL-1β. CT-005404 administered alone produced a dose-related increase in lever pressing in rats tested on a progressive ratio/chow feeding choice task. Atypical DAT inhibitors such as CT-005404 offer potential as a new avenue for drug treatment of motivational dysfunctions in humans. Highlights: The VMAT-2 inhibitor tetrabenazine alters effort-related choice behavior. CT-005404 is a novel atypical dopamine transport (DAT) inhibitor. The effort-related effects of tetrabenazine were blunted by CT-005404. The lever pressing suppression induced by IL-1β was blunted by CT-005404. CT-005404 increased selection of progressive ratio lever pressing vs. chow intake.